Psychological distress analysis among nurses during Covid-19 pandemic - Astuti, Rahmaniyah Dwi; Dewi, Ferina Ayu Kusuma; Iftadi, Irwan (Universitas Muhammadiyah Surakarta, 2022)
Abstract. During Covid-19 pandemic, the workload of nurses has become much higher. The condition of Covid-19 cases rate that continues to increase, adaptation to HSE measures and strict procedures to prevent transmission put great pressure on the health workers who are on duty. This study aims to measure the level of psychological distress in the form of stress, depression, and anxiety experienced by nurses at XYZ Hospital in Pemalang, Central Java using DASS 42 measuring instrument. The data analysis was processed using IBM SPSS Statistics 24 application with multiple linear regression method. The population is all nursing staff at XYZ Hospital, totaling 198 people. By using the stratified random sampling technique, a sample of 133 people was obtained consisting of 84 people from non-Covid-19 work units and 49 people from Covid-19 work units. Psychological distress factors are associated with internal factors (gender, age, years of service, education level, level of use of personal protective equipment) and external factors (level of PPE use, limited PPE, no PPE changing room facilities, lack of training, no zoning area, minimal formal psychological support, low social support, inadequate facilities and infrastructure, minimal information on the development of Covid-19, high working hours, fear of infection, chronic illness, trauma because the family has been exposed). The results showed that 75.2% of nurses experienced stress, 51.9% of nurses experienced depression, and 78.2% of nurses experienced anxiety disorders. The foremost vital factor influencing depression is age, anxiety is level of PPE use, and stress is length of time worked.Keywords: Covid-19 pandemic; DASS-42; nurses; psychological distress; SPSS